Mechanochemical synthesis of iron and cobalt magnetic metal nanoparticles and iron/calcium oxide and cobalt/calcium oxide nanocomposites - Chaudhary, Varun (2018)
We report an environmentally benign and cost‐effective method to produce Fe and Co magnetic metal nanoparticles as well as the Fe/Cao and Co/CaO nanocomposites by using a novel, dry mechanochemical process. Mechanochemical milling of metal oxides with a suitable reducing agent resulted in the production of magnetic metal nanoparticles. The process involved grinding and consequent reduction of low‐costing oxide powders, unlike conventional processing techniques involving metal salts or metal complexes. Calcium granules were used as the reducing agent. Magnetometry measurements were performed over a large range of temperatures, from 10 to 1273 K, to evaluate the Curie temperature, blocking temperature, irreversibility temperature, saturation magnetization, and coercivity. The saturation magnetizations of the iron and cobalt nanoparticles were found to be 191 and 102 emu g−1, respectively. The heating abilities of these nanoparticles suspended in several liquids under alternating magnetic fields were measured and the specific loss power was determined. Our results suggest that the dry mechanochemical process is a robust method to produce metallic nanoparticles and nanocomposites.